Fractional Contribution of Wildland Firefighters’ Personal Protective Equipment on Physiological Strain - Carballo-Leyenda, Belén; Villa, José G.; López-Satué, Jorge; Collado, Pilar S.; Rodríguez-Marroyo, Jose A. (Frontiers in Physiology, 2018)
Activities performed by wildland firefighters are carried out wearing a personal protective equipment (PPE). Although the PPE protects workers from a wide variety of hazards, it may increase their physiological response and limit their performance. The aim of this study was to analyze the effect of the protective clothing (PPC) and the rest of the PPE elements (i.e., helmet, neck shroud, gloves, goggles and mid-calf leather boots) on the wildland firefighters’ thermophysiological response during a moderate-intense exercise. Six male wildland firefighters performed, in a counterbalanced order, a 120 min graded exercise test wearing three different clothing configurations: i) a traditional short sports gear (SG), ii) a PPC and iii) a complete firefighters’ PPE. Trials were conducted on separate days at the same time of the day (12:00–15:00 h) and under climate-controlled conditions (~30ºC and ~30% relative humidity). Heart rate, respiratory gas exchange, gastrointestinal and skin temperature, blood lactate concentration were recorded throughout the tests. Additionally, parameters of heat balance were estimated. Exercise time was shorter (p < 0.001) wearing the PPE (62.4 ± 13.3 min) than with the PPC (115.5 ± 5.0 min) and SG (118.2 ± 20.7 min). The increment of gastrointestinal temperature with the PPE (1.8 ± 0.3 ºC) was greater (p < 0.05) than the observed in PPC (1.2 ± 0.6 ºC) and SG (1.0 ± 0.2 ºC). The use of PPC increased (p < 0.05) subjects’ metabolic demand and skin temperature versus SG during the last 20 min of the test. The sweat retention in the PPE (1,045.7 ± 214.7 g) and PPC (978.3 ± 330.6 g) was significantly higher than that obtained in the SG (510.0 ± 210.0 g). Sweat efficiency decreased (p < 0.05) in the following order: PPE (45.6 ± 18.3%), PPC (64.3 ± 7.8%) and SG (79.3 ± 7.0%). These results highlight the importance of the PPE elements in the subjects’ thermal strain. The reduction in the sweat evaporation produced by the PPE, together with the ensemble mass caused a substantial increase in the subjects’ thermophysiological response. As a consequence the performance was reduced by ~50%.